DESCRIPTIVE ANALYSIS OF REPRODUCTIVE QUALITY IN WORKING WOMEN IN THE STIKes RESPATI ENVIRONMENT - Danefi, Tupriliany; Lisnawati, Lilis (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2024)
Workers in Indonesia of reproductive age have various health problems. Female workers are more vulnerable than male workers, where women will experience menstruation, pregnancy, and menopause, which will make them more vulnerable if exposed to various risk factors in the work environment. Research results (1) say that women who work as full-time workers (35.24%) will be at risk of experiencing reproductive health problems, one of which is menstrual cycle problems. The research aims to determine the descriptive analysis of reproductive quality in working women in the STIKes Respati environment. The type of research is quantitative with descriptive methods, where the population is mothers who work at STIKes Respati. The research showed that weight examination for TB to determine nutritional status through the BMI measurement category showed that 70% had normal nutritional status, as many as 10% of workers were in the underweight category, and 20% were in the obese category. Based on the results of this research, the level of education is in line with a woman's ability to manage her diet well, so it impacts her nutritional status. Based on gynecological history, it is also at an expected average level with no history of gynecological disease in the family, as much as 80%. Meanwhile, the stress level of workers shows that 80% of workers show normal conditions (not stressed), and 20% are in stress conditions starting from mild to moderate stress.